Preform, preform method, and method for manufacturing compression bonded magnet
Patent Information
- Application Number
- JP2021107308
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-29
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2041-06-29
AI Technical Summary
Existing preformed bodies used in the production of compression bonded magnets tend to collapse and are difficult to transport due to their lack of shape retention properties.
A preformed body with a core-shell structure is developed, where the outer shell is formed by bonding a part of the magnet raw material, providing strength for shape retention and handling, while the inner core is in a low-density state suitable for manufacturing compressed bonded magnets.
The preformed body with a core-shell structure effectively retains its shape during transport and handling, ensuring high magnetic properties and efficient manufacturing of compression bonded magnets.
Smart Images

Figure 0007667426000002 
Figure 0007667426000003 
Figure 0007667426000004
Abstract
Description
[Technical field]
[0001] The present invention relates to preforms and the like used in the manufacture of compression bonded magnets. [Background technology]
[0002] Permanent magnets are often used in electromagnetic devices (electric motors, etc.) to save energy. There are two types of permanent magnets: sintered magnets, which are made by sintering magnetic powder, and bonded magnets, which are made by bonding magnetic powder with resin. Bonded magnets have a large degree of freedom in shape and are easier to mold than sintered magnets.
[0003] There are two main types of bonded magnets: injection bonded magnets, which are obtained by injecting a molten mixture of magnet powder and thermoplastic resin into a cavity and molding it, and compression bonded magnets, which are obtained by heating and compressing a mixture or kneaded product of magnet powder and thermosetting resin (simply called "magnet raw material") in a cavity.Compression bonded magnets usually have a higher proportion of magnet powder than injection bonded magnets, have high magnetic properties, and are also excellent in heat resistance because they use thermosetting resin.
[0004] Incidentally, when manufacturing compression bonded magnets, if powdered or granular magnet raw material is simply filled into a high-temperature cavity, the previously filled magnet raw material (especially the resin) may soften or melt, resulting in a decrease in filling efficiency and non-homogenization within the cavity (variable distribution of magnet particles and thermosetting resin). Therefore, a preform (temporarily compressed body) made by low-pressure molding powdered or granular magnet raw material is introduced into the cavity and subjected to heated compression molding (called "main molding"). For example, the following patent documents contain descriptions related to this: [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2013-256684 Summary of the Invention [Problem to be solved by the invention]
[0006] Patent Document 1 describes a method for producing a resin composition for bonded magnets at room temperature (unheated state) with a density of 0.1 to 0.2 t / cm 2 The pre-compressed compact obtained by low pressure molding (approximately 10-20 MPa) is fed into a high-temperature cavity placed directly below it without contact to produce a compression bonded magnet. Since the pre-compressed compact (pre-molded body) molded at low pressure in the room temperature range is prone to collapse and difficult to transport, Patent Document 1 deals with this by placing the pre-molding mold and the main molding mold close to each other above and below.
[0007] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a preform or the like of a new form having shape retention properties that enable transportation or the like. [Means for solving the problem]
[0008] As a result of intensive research into solving this problem, the inventor came up with the idea of a preform with a core-shell structure, and succeeded in obtaining a preform with the desired shape retention by warm compacting the magnet raw material. By expanding on this result, the inventor has completed the present invention, which will be described below.
[0009] 《Preformed body》 (1) The present invention is a preform having an outer shell formed by binding together a portion of powdered or granular magnet raw material which is a mixture or kneaded product of magnet particles and a thermosetting resin, and an inner encapsulation portion formed by the remainder of the magnet raw material within the outer shell.
[0010] (2) The preform of the present invention is not a homogeneous compressed powder of the magnet raw materials, but has a core-shell structure with an outer shell and an inner encapsulation part. The outer shell (shell) is formed by bonding (linking, bonding, etc.) a portion of the magnet raw materials, and provides the strength required for the preform to maintain its shape and handle. The inner encapsulation part (core) does not require such strength, and provides a low-density state suitable for the production of compression bonded magnets. The preform of the present invention can ensure both the ease of handling and the magnetic properties of a bonded magnet at a high level.
[0011] 《Preforming method》 The present invention can also be understood as a method for producing a preform. For example, the present invention may be a preform method including a preform step of warm-pressing a magnet raw material made of a mixture or kneaded product of magnet particles and a thermosetting resin.
[0012] <Manufacturing method of compression bonded magnets> The present invention can also be understood as a method for producing a compression bonded magnet. For example, the present invention may be a method for producing a compression bonded magnet comprising a main molding step of heating and compressing a preform.
[0013] Compression bonded magnets / magnetic components The present invention can also be understood as a compression bonded magnet, a magnetic member (electromagnetic member) in which a compression bonded magnet is integrally molded in a cavity of a housing, etc. Hereinafter, in this specification, the compression bonded magnet will be referred to simply as a "bonded magnet" as appropriate.
[0014] "others" Unless otherwise specified, "x to y" in this specification includes a lower limit value x and an upper limit value y. Any numerical value included in the various numerical values or numerical ranges described in this specification may be used as a new lower limit or upper limit value to create a new range such as "a to b". Furthermore, unless otherwise specified, "x to y μm" in this specification means x μm to y μm. The same applies to other unit systems (kA / m, kOe, etc.). [Brief description of the drawings]
[0015] [Figure 1] FIG. 4 is a scatter diagram showing the relationship between molding conditions of a preform and its apparent density. [Figure 2A] 1 is a photograph showing the appearance and fracture mode of a warm-formed preform. [Figure 2B] 1 is a photograph showing the appearance and fracture mode of a preform formed at room temperature. [Diagram 3] 4 is a photograph obtained by observing the outer surfaces of a preform formed at room temperature and a preform formed at warm temperature through a microscope. [Figure 4] This is a scatter diagram showing the effect of the apparent density and relative density of a preform on the orientation rate of a bonded magnet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] One or more components selected from the items described in this specification may be added to the above-mentioned configuration of the present invention. The components may be related to the manufacturing method or the product. Which embodiment is best depends on the target, required performance, etc.
[0017] 《Magnet raw materials》 The magnet raw material is a mixture or kneaded product of magnet particles (powder) and thermosetting resin (powder), and is in a powder or granular form. The mixture may be in a powder form obtained by mixing the thermosetting resin and magnet particles at room temperature, or in a granular form obtained by mixing the thermosetting resin and magnet particles while heating them. The kneaded product is in a granular form obtained by kneading (particularly by heating and kneading) magnet particles and thermosetting resin. The granular magnet raw material is made of composition particles (simply called "compound") in which the thermosetting resin is attached approximately uniformly to the surfaces of the magnet particles. In the kneaded compound, the thermosetting resin attached to the surfaces of the magnet particles is more likely to be dense than in the mixed compound. The thermosetting resin used to manufacture the compound does not have to be in a solid form (particulate form, etc.).
[0018] The thermosetting resin and magnet particles are heated, for example, in a warm state (for example, 40 to 120°C or 80 to 100°C). By mixing or kneading the thermosetting resin in a fluid state (softened or molten state), cracking of the magnet particles can be suppressed.
[0019] Magnetic Particles The magnetic particles may be of a single type or of multiple types. Multiple types of magnetic particles are obtained by mixing powders that differ in at least one of the following: alloy composition, particle size (particle size distribution), property (anisotropy / isotropy), etc.
[0020] The magnet particles may be, for example, a mixed powder of coarse powder and fine powder having different average particle sizes. The average particle size of the coarse powder is, for example, 40 to 200 μm, or 80 to 160 μm. The average particle size of the fine powder is, for example, 1 to 10 μm, or 2 to 6 μm. The average particle size is determined, for example, by measurement (measurement using the Fraunhofer method) using a laser diffraction particle size distribution measuring device (HELOS manufactured by Nippon Laser Corporation).
[0021] The mass ratio of the coarse powder to the total of the coarse powder and the fine powder (or the entire magnet powder) is, for example, 60 to 90 mass%, or 65 to 80 mass%. In other words, the mass ratio of the fine powder to that total is, for example, 10 to 40 mass%, or 20 to 35 mass%. The ratio of the magnet particles to the magnet raw material (the total of the magnet particles and the resin (including additives)) is, for example, 88 to 98 mass%, 91 to 95 mass%, or 92 to 94 mass%.
[0022] The magnet particles include, for example, rare earth magnet particles. The rare earth magnet particles include NdFeB type, which is based on Nd, Fe, and B, SmFeN type, which is based on Sm, Fe, and N, and SmCo type, which is based on Sm and Co. As an example, the magnet particles may be a mixture of coarse particles made of NdFeB type anisotropic magnet particles and fine particles made of SmFeN type anisotropic magnet particles or SmCo type anisotropic magnet particles. The magnet particles may include rare earth isotropic magnet particles and ferrite particles.
[0023] 《Thermosetting resin》 The thermosetting resin serves as a binder that holds the magnet particles. Thermosetting resins include epoxy resin, phenol resin, melamine resin, urea resin, and unsaturated polyester resin. A typical epoxy resin is, for example, a mixture of a base agent (prepolymer) and a curing agent, and is cured by forming a crosslinked network with epoxy groups. For example, novolac type, bisphenol A type, bisphenol F type, biphenyl type, naphthalene type, aliphatic type, and glycidylamine type are used as the base agent of the epoxy resin. For example, amine type, phenol type, and acid anhydride type are used as the curing agent of the epoxy resin. At least one of the base agent and the curing agent may be two or more types of resin. It is also possible to use a one-liquid epoxy resin whose thermal curing time can be adjusted by a curing treatment (thermal curing process).
[0024] The thermosetting resin may be a resin composition containing additives such as a curing accelerator and a mold release agent. In this specification, such a resin composition is also simply referred to as a "thermosetting resin". The magnet particles may be coated with a surfactant that is compatible with the thermosetting resin. In this specification, the magnet particles that have been subjected to such a surface treatment are also simply referred to as "magnet particles". Incidentally, examples of surfactants that are compatible with epoxy resins include titanate-based coupling agents and silane-based coupling agents.
[0025] 《Preformed body》 (1) The preform has an outer shell and an inner shell. The outer shell is made of a part of the magnet raw material (particularly a thermosetting resin) bound together. The inner shell is made of the remainder of the magnet raw material inside the outer shell.
[0026] The shell may be in a state where the magnet raw material particles (mixed magnet particles and thermosetting resin particles, or compound) are simply pressed together (compressed powder state). Furthermore, it is preferable that at least a part of the outer surface of the shell has a connecting portion where the thermosetting resin constituting the magnet raw material is integrated between a plurality of particles (between a plurality of thermosetting resin particles or between a plurality of compound particles). The connecting portion is formed, for example, when the thermosetting resin contacts the inner wall surface of a heated mold and softens or melts, and then resolidifies between adjacent particles of the magnet raw material. Naturally, the outer edge of the connecting portion where the thermosetting resin is integrated is expanded (enlarged) more than the outer edge of the thermosetting resin constituting the magnet raw material particles. The connecting portion may be a layer or film-like covering of the entire outer surface of the shell by the softened thermosetting resin spreading out, or may be an island-like scattering on the outer surface of the shell. It is preferable that the thermosetting resin in not only the inner capsule but also the outer shell is in a substantially uncured state with almost no progress in the curing reaction (crosslinking reaction).
[0027] The magnetic raw material of the encapsulated portion may be in a pressed powder state, a powder state, a granular state, or a mixture of these states. The closer the magnetic raw material of the encapsulated portion is to the state before preforming, the more improved the magnetic properties of the bonded magnet can be.
[0028] The preform may have a true density (ρ 0 The relative density (ρ / ρ 0 ) are 48-72%, 50-70%, and 55-65%. The true density is determined from the respective densities and blend ratios of the magnet particles and thermosetting resin that make up the magnet raw material. The apparent density is determined by dividing the mass of the preform by its apparent volume (for example, the volume calculated from the external dimensions).
[0029] (2) The preform is obtained, for example, by warm pressure molding the magnet raw material (preforming step). The preforming step may be performed, for example, by setting the preforming temperature (Tp), which is the temperature of the inner wall surface of a preforming mold into which the magnet raw material is filled, to ts≦Tp≦ts+20°C, or even ts+5°C≦Tp≦ts+15°C (ts: softening point of the thermosetting resin).
[0030] As a method for measuring the softening point, there are the ring and ball method (ASTM D36) and the cup and ball method (ASTM D3461). In both methods, a weight is placed on the material filled in a cylindrical container and heated, and the temperature at which the extrusion amount of the softened material by the weight reaches a predetermined value is defined as the softening point.
[0031] The softening point (ts) according to the present invention may be the measured value or the softening point described in a catalog or the like. Further, when the thermosetting resin is a resin composition composed of a plurality of resins, the softening point (ts) may be a softening point calculated according to the composite rule from the blending ratio of each resin (for example, the main agent and the curing agent) and their known softening points.
[0032] Furthermore, when the thermosetting resin is composed of a plurality of resins, the intermediate temperature of the softening points of each resin may be used as the preforming temperature (Tp). For example, when the thermosetting resin contains at least a first resin having a first softening point (ts1) and a second resin having a second softening point (ts2) higher than the first softening point, the preforming temperature (Tp), which is the temperature of the inner wall surface of the preforming mold filled with the magnet raw material, may satisfy ts1 ≦ Tp ≦ ts2, and the preforming process may be performed. When the thermosetting resin is composed of three or more resins having different softening points, the selection of the first softening point (first resin) and the second softening point (second resin) is arbitrary.
[0033] When the thermosetting resin is composed of a plurality of resins, and among their softening points, the first softening point (ts1) is the minimum and the second softening point (ts2) is the maximum, the preforming temperature (Tp) may be higher than the first softening point and lower than the second softening point (ts1 < Tp < ts2). In other words, the preforming temperature (Tp) may be the intermediate temperature between the minimum softening point (tsm1) and the maximum softening point (tsm2) (tsm1 < Tp < tsm2).
[0034] When the preforming temperature is near the softening point of the thermosetting resin, it becomes easy to adjust the molding pressure and molding time related to the preforming process. If the preforming temperature is too low or too high with respect to the softening point, it becomes difficult to form the desired outer shell portion and inner inclusion portion.
[0035] The preforming step may be performed at a molding pressure of, for example, 0.1 to 100 MPa, 0.5 to 50 MPa, or even 1 to 10 MPa. If the molding pressure is too low, molding the preform itself is difficult. If the molding pressure is too high, the magnet particles may crack, the density of the preform may increase, etc.
[0036] In the preforming step, a molding time of, for example, 1 to 20 seconds, or even 1 to 5 seconds, is sufficient. By keeping the molding time relatively short, a preform having the desired outer shell and inner capsule can be efficiently obtained.
[0037] (3) The preform may be in any form that allows it to be filled, loaded, or cast into the cavity in which the bonded magnet will be molded. The preform may be a one-piece body that approximates the bonded magnet, or it may be a divided body that is subdivided according to the bonded magnet. The shape of the preform should match the shape of the cavity in the main molding process. Usually, a different mold is used for the preform process than for the main molding process.
[0038] 《Main molded body / Main molding process》 (1) The main compact that becomes the bonded magnet is obtained by heating and compressing a preform in a cavity (main compacting process). When the magnet raw material contains anisotropic magnet particles (particularly rare earth anisotropic magnet particles), the main compacting process is preferably carried out by applying an aligning magnetic field to the cavity in which the preform is placed.
[0039] The molding pressure (compressive force) is, for example, 5 to 500 MPa, 10 to 250 MPa, 20 to 100 MPa, or even 30 to 50 MPa. Excessive compression force can cause deformation of the bonded magnet or cavity, and cracking of the magnet particles (particularly particles obtained by hydrogen treatment (HDDR, d-HDDR) of the magnet alloy). As long as the compression force is not too small, even low-pressure molding (for example, 100 MPa or less) can produce a bonded magnet that exhibits high Br and high Hk. Hk represents the magnitude of the reverse magnetic field at a magnetic flux density equivalent to 90% of Br (residual magnetic flux density), and is an index of the effective magnetic flux density against the reverse magnetic field or the squareness of the magnetization curve (JH curve).
[0040] The molding temperature (heating temperature) is, for example, 120 to 200°C, or even 130 to 170°C. If the heating temperature is too low, the thermosetting resin will not soften or melt sufficiently, which may lead to cracking of the magnet particles and a decrease in the orientation rate. If the heating temperature is too high, the thermosetting resin will harden prematurely, the magnet particles will deteriorate due to oxidation, etc., and this will lead to a decrease in the magnetic properties of the bonded magnet.
[0041] The aligning magnetic field is usually applied in a direction that crosses (or is perpendicular to) the compression direction of the preform (magnet raw material). Canada The magnitude of the aligning magnetic field is, for example, 0.5 to 3 T, or even 1 to 2 T. The aligning magnetic field is the magnetic flux density on the inner peripheral surface of the cavity in which the bonded magnet is molded. The magnetomotive source of the aligning magnetic field may be either an electromagnet or a (rare earth) permanent magnet.
[0042] (2) The bonded magnet may be the present compact as is, or may be the present compact that has been subjected to a heat treatment (curing treatment) to harden the resin and magnetized. The curing treatment is performed by heating the present compact at a temperature according to the type of thermosetting resin. The heating temperature is, for example, 130 to 250°C, or 150 to 230°C.
[0043] Magnetization may be performed, for example, by applying a magnetic field of about 2 to 6 T. Note that bonded magnets that have been heat-compression molded in an aligning magnetic field do not necessarily have to be magnetized, but magnetization is expected to improve the magnetic properties of the bonded magnet.
[0044] The bonded magnet may be one that has been removed (ejected) from the cavity after the main molding process, or one that has been integrated with a housing having a cavity (slot, etc.) during the main molding process. An example of a magnetic component in which a bonded magnet is integrated into a cavity of a housing is the field element (rotor, stator) of an electric motor (motor for driving a vehicle, motor for air conditioner, motor for home appliances, etc.). The electric motor may be either a DC motor or an AC motor. Furthermore, the electric motor includes not only motors but also generators. EXAMPLES
[0045] A number of preforms (samples) were produced by changing the molding conditions in various ways. The preforms were then used to produce bonded magnets. Their appearances and properties were evaluated. The present invention will be described in detail below based on these specific examples.
[0046] <Sample Preparation> (1) Magnet powder and thermosetting resin The magnet powders used were a commercially available NdFeB-based anisotropic magnet powder (Magfine, manufactured by Aichi Steel Corporation; Br: 1.28 T, iHc: 1313 kA / m, average particle size: 125 μm), which is a coarse powder produced by hydrogen treatment (d-HDDR), and a commercially available SmFeN-based anisotropic magnet powder (SmFeN alloy fine powder, manufactured by Sumitomo Metal Mining Co., Ltd.; C / Br: 1.35 T, iHc: 875 kA / m, average particle size: 3 μm), which is a fine powder.
[0047] As the thermosetting resin, an epoxy resin consisting of a base resin (first resin) and a curing agent (second resin) shown in Table 1 was used. Both were in powder form at room temperature. Furthermore, in this example, a resin composition was prepared by blending the epoxy resin with a curing accelerator and a mold release agent (both collectively referred to as "additives") shown in Table 1. In this specification, a resin composition containing an additive is also simply referred to as an "epoxy resin."
[0048] The resin composition placed on the hot plate began to deform (soften) when the surface temperature of the hot plate reached about 60° C. The softening point was calculated from the softening point of the base resin (ts1) and the softening point of the curing agent (ts2) and their blending ratio: ( The temperature was approximately 53℃×100+65℃×74.4) / (100+74.4) ≒ 58.1℃ (approximately 59℃).
[0049] (2) Magnet raw materials A mixture of magnet powder (coarse powder and fine powder) and thermosetting resin was mixed while heating in a kneader (suitably referred to as "melt mixing") to prepare a granular compound (kneaded material / magnet raw material). The blending ratio of the mixture, in terms of mass percentage relative to the total, was coarse powder: 65.2 mass%, fine powder: 27.9 mass%, thermosetting resin (including additives): 6.9 mass%. The true density (ρ0) of the magnet raw material calculated from the true density of each and the blending ratio was 5.6 g / cm 3 It becomes.
[0050] Incidentally, in terms of volume ratio, the ratio of magnet powder (coarse powder and fine powder) to thermosetting resin is 7:3. The volume ratio of coarse powder to fine powder is almost the same as their mass ratio, 7:3.
[0051] The kneading was carried out for 5 minutes by keeping the kneader at 90°C and rotating the kneader at a low speed (10 rpm) (melt mixing process). At this time, the thermosetting resin was in a softened or molten state. However, because this was melt mixing at a low temperature for a short period of time, the thermosetting resin was hardly thermally cured.
[0052] (3) Preforming process The compound was loaded into the cavity of a preforming mold to produce a rectangular parallelepiped (top and bottom surfaces: 13.8 mm square). The temperature of the inner wall of the cavity (mold side wall temperature) was set to approximately 23°C (room temperature), 60°C or 65°C (warm), or 150°C (hot). These temperatures were measured by a thermocouple embedded near the inner wall of the mold. For each temperature, the molding pressure (0.15 to 500 MPa) was changed.
[0053] (4) Main molding process Each warm-molded preform was placed in the cavity of the main mold and compression molded in a heated aligning magnetic field. At this time, the inner wall surface temperature of the cavity was 150°C, and the molding pressure (compressive force): 20 MPa. The orientation direction was the direction (horizontal direction) perpendicular to the compression direction (axial direction), and the aligning magnetic field (5-18 kOe / 398-1432 kA / m) was variously changed. In this way, a rectangular solid (top and bottom faces: 14 mm square) main molded body was obtained.
[0054] As a comparative sample, a granular compound was directly charged into the cavity of the main molding die without using a preform, and a main molding was similarly produced by heat compression molding in an aligning magnetic field.
[0055] (5) Heat treatment process The molded body was removed from the mold cavity and heated in air at 150°C for 30 minutes (curing process). In this way, bonded magnets were obtained by thermally curing the thermosetting resin. Each bonded magnet was also magnetized by applying a magnetic field of 6T using an air-core coil (magnetization process).
[0056] Observation and Measurement (1) Forming pressure and apparent density (ρ) of preformed body The apparent density (ρ) of each preform with different molding temperatures and pressures was determined. The apparent density was calculated by measuring the mass and dimensions of each preform and dividing the mass by the volume calculated from the dimensions. The relationship between these values is shown in Figure 1.
[0057] (2) Appearance and fracture mode of preformed body Warm-formed preform (ρ=3g / cm 3 ) and a preform molded at room temperature (ρ = 3g / cm 3 The appearance and fracture mode of the preform are shown in Figure 2A and Figure 2B (collectively referred to as "Figure 2"). The fracture mode shows the state when the preform is lightly struck with a plastic hammer.
[0058] The outer surfaces of the preforms were observed using an optical microscope. The observed images of each preform are also shown in Figure 3. The boundary (outer edge) of the resin that appeared on the surface (part) of each preform is indicated by a solid line or a dashed line.
[0059] (3) Orientation rate of bonded magnets The orientation rate was calculated from the magnetic properties of the bonded magnet. The orientation rate, the aligning magnetic field in the main compacting process, and the apparent density of the preform (ρ[g / cm 3 ]) or relative density (%) are summarized in Figure 4.
[0060] Here, the magnetic properties of the bonded magnets were determined from the BH curves obtained by room temperature measurements using a DC BH tracer (TRF-5BH-25Auto manufactured by Toei Kogyo Co., Ltd.). 0 [%]) is the apparent density (ρ) of the preform divided by the true density (ρ 0 ) to obtain the result.
[0061] The orientation rate was calculated by dividing the residual magnetic flux density (Brx) when each orienting magnetic field (kOe) was applied by the residual magnetic flux density (Br0) when an orienting magnetic field of 20 kOe (1591 kA / m) was applied.
[0062] "evaluation" (1) Apparent density of preform As can be seen from Figure 1, the bulk density (ρ: 2.4 g / cm 3 ) of the powdered compound was increased by warm low pressure molding. 3 A preform with an apparent density close to the bulk density of the powder was obtained.
[0063] (2) Shape retention of preformed bodies As can be seen from Figure 2A, the warm-molded preform had an outer shell, and the compound inside (the envelope / core) was granular. On the other hand, as can be seen from Figure 2B, the room-temperature molded preform had no outer shell, and even a slight impact caused the whole to collapse into granular form.
[0064] Such a difference is believed to be due to the morphology of the thermosetting resin (presence or absence of connecting parts) near the outer surface of the preform, as shown in FIG.
[0065] (3) Orientation rate of bonded magnets As can be seen from Figure 4, regardless of the magnitude of the aligning magnetic field, the lower the apparent density of the preform, the higher the orientation rate of the bonded magnet. 3 It was also found that the orientation rate of the bonded magnet made using the preform was almost the same as that of the bonded magnet made using the granular compound as is.
[0066] From the above, it has been found that a preform having an outer shell and an inner encapsulation portion can ensure shape retention (and therefore handleability) while suppressing the deterioration of the magnetic properties of the bonded magnet.
[0067] [Table 1]
Claims
1. an outer shell portion formed by binding together a part of a powdered or granular magnet raw material made of a mixture or kneaded product of magnet particles and a thermosetting resin; an inner shell portion formed of the remainder of the magnet raw material; A preform used in the manufacture of a compression bonded magnet having the following properties:
2. 2. The preform according to claim 1, wherein at least a portion of an outer surface of the outer shell portion has a connecting portion where a plurality of particles of the thermosetting resin are integrated together.
3. 3. The preform according to claim 1, wherein at least a portion of the inner portion is in a powder or granular form.
4. 4. The preform according to claim 1, wherein the magnet particles are contained in an amount of 88 to 98 mass % based on the total amount of the magnet raw material.
5. 5. The preform according to claim 1, wherein the magnet particles include rare earth anisotropic magnet particles.
6. True density (ρ 0 The relative density (ρ / ρ 0 6. The preform according to claim 1, wherein the content of the porosity is 48 to 72%.
7. A preforming process is provided for warm pressure forming a magnet raw material made of a mixture or kneaded product of magnet particles and a thermosetting resin, A preforming method which provides the preform according to any one of claims 1 to 6.
8. 8. The pre-forming method according to claim 7, wherein the pre-forming step is performed by setting a pre-forming temperature (Tp), which is a temperature of an inner wall surface of a pre-forming mold into which the magnet raw material is filled, to a softening point (ts) of the thermosetting resin to the softening point + 20°C (ts≦Tp≦ts+20°C).
9. The thermosetting resin includes at least a first resin having a first softening point (ts1) and a second resin having a second softening point (ts2) higher than the first softening point, 8. The pre-forming method according to claim 7, wherein the pre-forming step is performed by setting a pre-forming temperature (Tp), which is a temperature of an inner wall surface of a pre-forming mold into which the magnet raw material is filled, to a value between the first softening point and the second softening point (ts1≦Tp≦ts2).
10. Among the softening points of the resins constituting the thermosetting resin, the first softening point (ts1) is the smallest and the second softening point (ts2) is the largest, The preforming method according to claim 9, wherein the preforming temperature (Tp) is greater than the first softening point and less than the second softening point (ts1<Tp<ts2).
11. A method for producing a compression bonded magnet, comprising a main molding step of heat-compressing and molding the preform according to any one of claims 1 to 6.
12. the magnet particles include anisotropic magnet particles; The method for producing a compression bonded magnet according to claim 11, wherein the main compacting step is performed by applying an aligning magnetic field to a cavity containing the preform.
Citation Information
Patent Citations
Resin-bonded rare-earth magnet
JP2000124019A
Yoke integrated bond magnet and magnet rotor for motor therewith
JP2007236113A
Method for manufacturing soft magnetism composite consolidated core
JP2009164317A
Method of manufacturing bonded magnet
JP2013256684A
Yoke-integrated bonded magnet and magnet rotator for motor using the same
US20090085416A1